CHARACTERIZATION STUDY OF CHITOSAN AS METAL IONS REMOVAL - Mohd Zaid, Mirza (Universiti Teknologi Petronas, 2005)
Removal of certain metal ions from wastewaterby using biopolymers is proved to be a great alternative at the moment. Chitosan is one of the best examples in removing heavy metal ions. Its high amino content has been found to possess good sorptive capacities for many heavy metal ions through complexion of heavy metal ions with the amine group in chitosan. Chitosan indicates a family of deacetylated chitins. Chitin ((l-4)-linked 2-acetamido-2-deoxy-p-D-glucan) is widely distributed among invertebrates. Chitin is extracted from crab shells through demineralization and deproteination process. Chitosan is obtained by deacetylation of chitin in concentrated sodium hydroxide (NaOH). The efficiency of metal ions removal using chitosan is tested against oily wastewater. The presence of metal ions in sample solution is measured using Flame Atomic Absorption Spectrometry (FAAS). The weight percentage of chitin extracted from crab shells powder is 45.51 wt %. The weight percentage of chitosan yield from the deacetylation process is 69.94 wt %. The study of the influence of dose of chitosan and effect of contact time gives the expected result. As the dose of chitosan added to the sample oily wastewater increases, the percentage removal of metal ions also increases. The percentage removal of zinc, lead and iron at optimum doseof chitosan addedis 89.08%, 84.00%, and 61.36% accordingly. Increasing the contact time also results in increases of percentage removal of metal ions. The percentage removal of zinc, lead, and iron at optimum contact time is 93.70%, 78.85%, and 65.58% accordingly. From the results obtained, the selectivity of chitosan to metal ions decreased in order Zn > Pb > Fe2+.